Menguak Esensi: Negara Hukum dalam Konstitusi: Sebuah Analisis Mendalam terhadap Perlindungan Hak-hak Warga Negara - Wulandari S, Lestari; Tanggahma, Biloka; Muhammad, Rivaldhy N. (UNES Law Review, 2024)
This study aims to investigate the essential role of the rule of law within the framework of a nation's constitution. Its focus lies in how the constitution provides a solid foundation for safeguarding the rights of citizens. The research objective is to gain a deeper understanding of how the rule of law ensures justice, freedom, and the protection of human rights for all citizens. This endeavor will aid in identifying the strengths and weaknesses within existing systems of constitutional law. Employing a thorough approach to legal and constitutional analysis, the study involves critical reviews of constitutions, legal regulations, and court decisions related to the protection of citizens' rights. Data will be gathered from primary and secondary sources, including legal documents, academic literature, and judicial rulings. The expected outcome of this research is to provide better insights into how the rule of law can function as a guardian of justice and human rights enforcement. This in-depth analysis is anticipated to lay the groundwork for further debate on the role of the rule of law in building a fair and inclusive society.